2015
DOI: 10.1186/s12889-015-1634-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between parents’ subjective time pressure and mental health problems among children in the Nordic countries: a population based study

Abstract: BackgroundThe home, the family and the parents represent a context of everyday life that is important for child health and development, with parent-child relationships highlighted as crucial for children’s mental health. Time pressure is an emerging feature of modern societies and previous studies indicates that parents with children living at home experience time pressure to a greater extent than people with no children living at home. Previous studies of children’s mental health in relation to parents’ time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…In the model, we considered two work-related time use activities (housework and paid work), measured in hours per day, as these activities are associated with stress, depression and physical health status [ 26 , 36 , 45 ]. We also included marital status (married/cohabiting vs single/widowed) and age which previous studies have found to be associated with stress and general health status [ 46 ]. To investigate work-related time use activities and potential “stress buffers”, we used time devoted to social activities [ 41 ], (measured in hours per day) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In the model, we considered two work-related time use activities (housework and paid work), measured in hours per day, as these activities are associated with stress, depression and physical health status [ 26 , 36 , 45 ]. We also included marital status (married/cohabiting vs single/widowed) and age which previous studies have found to be associated with stress and general health status [ 46 ]. To investigate work-related time use activities and potential “stress buffers”, we used time devoted to social activities [ 41 ], (measured in hours per day) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, researchers have investigated relationships between chronic time pressure and psychological well-being. A notable example is Gunnarsdottir et al (2015), who found an association between parents’ subjective time pressure and increased mental health problems among children. Acknowledging that chronic time pressure is an unavoidable experience of daily life in industrialized societies, several studies have examined the effectiveness of alleviating strategies and therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to find someone who has not experienced this type of stress (1). Huge amounts of money are lost as a result of a variety of factors, such as lack of physical and mental health among the staff, efficiency deduction, job quitting and job changing, that mainly happen because of job-related stress (2,3). It is believed that every year, stress and stress-related problems waste hundreds of working days, and in average, everyday one person avoids going to work because of stress disorders and diseases (4).…”
Section: Introductionmentioning
confidence: 99%